2015
DOI: 10.1118/1.4928603
|View full text |Cite|
|
Sign up to set email alerts
|

Statistical iterative reconstruction to improve image quality for digital breast tomosynthesis

Abstract: Purpose: Digital breast tomosynthesis (DBT) is a novel modality with the potential to improve early detection of breast cancer by providing three-dimensional (3D) imaging with a low radiation dose. 3D image reconstruction presents some challenges: cone-beam and flat-panel geometry, and highly incomplete sampling. A promising means to overcome these challenges is statistical iterative reconstruction (IR), since it provides the flexibility of accurate physics modeling and a general description of system geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
0
19
0
2
Order By: Relevance
“…13 To minimize patient exposure while optimizing the utility of the radiation dose, a normal-dose/high-quality scan can be performed first to establish a reference, followed by a series of low-dose CT (LDCT) scans. The LDCT scans can be reconstructed independently by statistical image reconstruction (SIR) methods [14][15][16][17][18][19][20][21][22][23] to suppress noise and streak artifacts, using information from current acquisition only. Nevertheless, the previously acquired normal-dose image can be exploited as prior information due to similarities between the normal-dose image and the series of reconstructed images from these scans.…”
Section: Introductionmentioning
confidence: 99%
“…13 To minimize patient exposure while optimizing the utility of the radiation dose, a normal-dose/high-quality scan can be performed first to establish a reference, followed by a series of low-dose CT (LDCT) scans. The LDCT scans can be reconstructed independently by statistical image reconstruction (SIR) methods [14][15][16][17][18][19][20][21][22][23] to suppress noise and streak artifacts, using information from current acquisition only. Nevertheless, the previously acquired normal-dose image can be exploited as prior information due to similarities between the normal-dose image and the series of reconstructed images from these scans.…”
Section: Introductionmentioning
confidence: 99%
“…One potential limitation of this work is that we demonstrated through‐plane blurring artifacts in DBT images could be reduced, resulting in a significant reduction in anatomical clutter when a specific SIR implementation is used; yet we have not demonstrated this can be achieved with other SIR methods in general. However, work from many other groups has previously shown that a reduction in through‐plane blurring artifacts can be achieved using other SIR methods . Based upon our finding in this paper that the reduced anatomical clutter is associated with the reduction of through‐plane blurring artifacts, it is anticipated that other SIR methods might also be used to reduce anatomical clutter as long as the parameters in these alternative methods are optimized to achieve the goal of through‐plane artifacts reduction.…”
Section: Discussionmentioning
confidence: 79%
“…Given the argument that a reduction in through‐plane artifacts level would lead to a potential reduction in anatomical clutter and previous results from other investigators demonstrated that a reduction of through‐plane artifacts can be achieved in DBT with some statistical image reconstruction (SIR) methods, one may wonder, if the use of SIR in DBT would result in a more pronounced reduction in β values than β ≈3.1 from the current clinical reconstructions? If the answer is yes, then what would be the quantitative β values for a specific SIR?…”
Section: Introductionmentioning
confidence: 97%
“…A location-dependent weighting (Xu et al 2015) of the penalty function was applied to encourage more uniform resolution, and the regularization parameter β =5 e − 2 was chosen to qualitatively achieve a comparable resolution to FBP. The initial guess for the background anatomy for KCR was the FBP volume truncated at an upper value of 0.03 mm −1 (in a coarse attempt to remove the pedicle screw from the anatomy).…”
Section: Methodsmentioning
confidence: 99%